Prof. N.F. Katanov and his contribution to the research of ethnography and folklore of Turkic people in Central Asia - Tuguzhekova, Valentina N.; Valeev, Ramil M. (The New Research of Tuva, 2011)
Article summarized main data of biography and scientific activities of the outstanding turkologist N.F. Katanov (1861–1922) including his fieldworks, publications, ethnoses and cultures he has examined and fundamental publications about the scientist until the present day – presenting the katanovology.